Calibration methodology for predictive simulation of sub-0.13 technology CMOS device's performance - Leong, Vincent Kum Woh. (2008)
This report describes a calibration methodology for predictive simulation of sub-0.13 pm technology CMOS device’s performance. It provides an introduction to TCAD simulators (TSUPREM4 and MEDICI) and reviews the physical models and parameters that are implemented in this calibration methodology. These include models and parameters for process simulation in Ion Implantation, Diffusion of Impurities, Activation of Impurities, Polycrystalline Materials Modeling and Quantum Mechanical Modeling. Models for device simulation are Shockley-Read- Hall and Auger Recombination, Lombardi Surface Mobility, Parallel Field Mobility and Modified Local Density Approximation Quantum Effect. Preparation procedures in Process Flow, Recipes, Physical Device Structures, Implantation Profiles and Grid Setting are also highlighted in order to construct reliable simulation decks.